2008
DOI: 10.1007/bf03168241
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hyperoxia on biomarkers of oxidative stress in closed-circuit oxygen military divers

Abstract: Oxygen toxicity is a problem in diving which can have fatal consequences in the water. When divers use closed-circuit oxygen rebreathing apparatus they are taking only oxygen 100% and this hyperoxic exposure increases the generation of reactive oxygen species (ROS) in biological tissues. The objective of the present study is to evaluate the effects of hyperoxia on biomarkers of oxidative stress in closed-circuit oxygen military divers. Fifteen professional divers of Spanish Navy Diving Centre participated in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
3
10
0
2
Order By: Relevance
“…This is in accordance with previous studies where no changes in lipid peroxidation or oxidative stress marker were reported in patients with various pathologies [37]. Moreover, Alcaraz-García et al reported that, in professional divers, HBO 2 training (~1.7 ATA; 100% O 2 ) for 2-3 times per week during 12 weeks did not induce an important oxidative hyperoxia-induced stress due an adaptive process [38]. Taken together, these data suggest that training in a HBO 2 environment does not modify oxidative stress in human volunteers.…”
Section: Discussionsupporting
confidence: 91%
“…This is in accordance with previous studies where no changes in lipid peroxidation or oxidative stress marker were reported in patients with various pathologies [37]. Moreover, Alcaraz-García et al reported that, in professional divers, HBO 2 training (~1.7 ATA; 100% O 2 ) for 2-3 times per week during 12 weeks did not induce an important oxidative hyperoxia-induced stress due an adaptive process [38]. Taken together, these data suggest that training in a HBO 2 environment does not modify oxidative stress in human volunteers.…”
Section: Discussionsupporting
confidence: 91%
“…Measurements of specific F 2 -isoprostanes in urine may provide a sensitive biochemical end point for dosefinding studies of natural and synthetic inhibitors of lipid peroxidation. We have measured this lipid peroxidation biomarker in a young healthy Spanish population, and although it has been a relatively small [1,3]. We think that these differences can be explained due to the difference in ages of the patients.…”
Section: Discussionmentioning
confidence: 88%
“…For example, the oxidative stress that occurs in the hyperventilation syndrome can be cured by learning DB. Hyperventilation, in fact, induces hyperoxia which is known to be related with oxidative stress [81, 82]. The hyperventilation syndrome affects 15% of the population and occurs when breathing rates elevate to 21–23 bpm as a result of constricted non-DB.…”
Section: Discussionmentioning
confidence: 99%